2004
DOI: 10.1590/s1676-24442004000100003
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of wild-type rubella virus in fibrochondrocyte cells

Abstract: This study describes the rapid growth of the rubella virus in samples of a primary fibrochondrocyte cell culture with the development of a cytopathic effect (CPE), in response to infection by the rubella virus. The cells were isolated from the meniscus joint of a rabbit after enzymatic extraction and incubated at 37°C with a Dulbecco's modified Eagle's medium (DMEM), supplemented with 10% fetal calf serum. A total of six clinical samples from urine, blood and cerebrospinal fluid were inoculated in the fibrocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Although virus isolation is time‐consuming, labor‐intensive, and not particularly sensitive, it is still recommended by the WHO [2007] for studying the etiology and epidemiology of rubella. RV can be cultured in a variety of cell lines, such as RK13, SIRC, BHK, and Vero (Vero/SLAM) cells, but serial propagation can be established only in a limited number of cell lines [Figueiredo et al, 2004]. Previous studies have shown that specific CPE may appear in RK13 cells under controlled conditions, or in RK13 and SIRC cells after one or two passages in Vero cells [Figueiredo et al, 2000; Best et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Although virus isolation is time‐consuming, labor‐intensive, and not particularly sensitive, it is still recommended by the WHO [2007] for studying the etiology and epidemiology of rubella. RV can be cultured in a variety of cell lines, such as RK13, SIRC, BHK, and Vero (Vero/SLAM) cells, but serial propagation can be established only in a limited number of cell lines [Figueiredo et al, 2004]. Previous studies have shown that specific CPE may appear in RK13 cells under controlled conditions, or in RK13 and SIRC cells after one or two passages in Vero cells [Figueiredo et al, 2000; Best et al, 2005].…”
Section: Introductionmentioning
confidence: 99%